ps-TRIR Covers All the Bases - Recent Advances in the Use of Transient IR for the Detection of Ultrafast Species in DNA - KELLY, JOHN (My University, 2009)
Recent developments of the picosecond transient absorption infrared technique and its ability to elucidate the nature and kinetic behaviour of transient species formed upon pulsed laser excitation of nucleic acids are described.
PUBLISHED
Keywords: kinetic behaviour; kinetic behaviour; Genes & Society